SOME ALGORITHMS FOR RECONSTRUCTION CT IMAGES: Sarvarbek POLVONOV, Alibek ABDUAKHADOV, Jamshid ABDUGʻANIYEV, Gʻulomjon ELMURATOV - Maqola, Tezis (Центр Научных Публикаций (buxdu.uz), 2022)
In computed tomography, the tomography reconstruction problem is to obtain a tomographic slice image from a set of projections. A projection is formed by drawing a set of parallel rays through the 2D object of interest, assigning the integral of the object’s contrast along each ray to a single pixel in the projection. In this work we demonstrate some reconstruction algorithm by Python. Key words: Computed tomography (CT), Fourier transform,